1958. Antiviral Effects, Pharmacokinetics (PK), and Safety of the Respiratory Syncytial Virus (RSV) Fusion Protein Inhibitor, JNJ-53718678 (JNJ-8678), in RSV-infected Infants With Bronchiolitis, in the Phase 1b Study 53718678RSV1005. (26th November 2018) - Martinon-Torres, Federico; Rusch, Sarah; Huntjens, Dymphy; Remmerie, Bart; Vingerhoets, Johan; McFadyen, Katie; Ferrero, Fernando; Baraldi, Eugenio; Conejo, Pablo Rojo; Epalza, Cristina; Stevens, Marita
Abstract: Background: JNJ-8678 is a RSV-specific fusion inhibitor and a potential new treatment for respiratory infections caused by RSV. Data from a Phase 1b study of PK, safety and antiviral effects in hospitalized RSV-infected infants are presented. Methods: 37 and 7 patients, respectively, were randomized to JNJ-8678 (ascending doses, Table) or placebo (PBO) treatment once daily for 7 days. PK assessments were based on sparse sampling using a population PK model in adults scaled for pediatrics, accounting for allometric principles and maturation of drug clearance pathways. Safety was evaluated by AE reporting, lab and ECG assessments. Antiviral activity was assessed by measuring viral load (VL) using a quantitative RT-PCR assay for RSV RNA from nasal swabs. Results: Sparse PK data are described by an integrated PK model (table) and indicated PK parameters for different dose levels were similar across age groups. Treatment with JNJ-8678 appeared to reduce VL more rapidly than PBO (figure). Median change in VL from baseline (BL) in JNJ-8678-treated patients (combined dose groups) vs. PBO was −1.98 vs. −0.32 log10 copies/mL at Day 3. Mean differences in change from BL (90% CI) of JNJ-8678 (combined dose groups) vs. PBO on Days 2 and 3 were estimated −1.33 (−2.26; −0.39) and −1.62 (−2.55; −0.69) log10 copies/mL, respectively (general linear model, adjusted for BL VL; P ≤ 0.05). There was a clear separation between JNJ-8678 and PBO, but no evident exposure–response relationship. JNJ-8678 was generally well tolerated with no new safety signals compared with adults and no dose relationship with AEs or lab abnormalities were observed. Conclusion: This dataset in RSV-infected infants showed a clear trend for an early antiviral effect of JNJ-8678, which was similar across dose groups. JNJ-8678 treatment was generally well tolerated. Disclosures: F. Martinon-Torres, Pfizer: Consultant, Consulting fee. SPMSD: Consultant, Consulting fee. GSK: Consultant, Consulting fee. S. Rusch, Janssen: Employee and Shareholder, Salary. D. Huntjens, Janssen: Employee and Shareholder, Salary. B. Remmerie, Janssen: Employee and Shareholder, Salary. J. Vingerhoets, Janssen: Employee and Shareholder, Salary. K. McFadyen, Janssen: Employee and Shareholder, Salary. E. Baraldi, Abbvie: Lectures, Speaker honorarium. Chiesi Farmaceutici: Consultant, Consulting fee. Novartis: Consultant, Consulting fee. Janssen: Consultant, Consulting fee. M. Stevens, Janssen: Employee and Shareholder, Salary.